COMPUTER DIDACTIC GAMES IN ORGANIZING THE EDUCATIONAL PROCESS - Gulnoz Turayeva (Scholar Express Journal, 2023)
Didactic games aimed at educational purposes occupy an important place among modern psychological and pedagogical learning technologies. This article provides information about the technologies of computer didactic games based on information communication tools, their implementation of functions and roles in the educational process.
Keywords: computer didactic games; information technology